Global profiling of N-terminal cysteine–dependent degradation mechanisms - Aizat Bekturova; Yaara Makaros; Shahar Ben-David; Itay Koren (Proceedings of the National Academy of Sciences, 2025)
Hypoxia, a condition characterized by insufficient oxygen supply, challenges cellular homeostasis and energy production, triggering adaptive responses to promote survival under these stressful conditions. One key strategy involves enzymatic oxidation of N-terminal cysteine residues coupled with proteolysis through the Cys-Arg/N-degron pathway. Despite hundreds of human proteins possessing N-terminal cysteine, very few have been identified as substrates of this pathway, and its substrate selectivity remains unclear. Moreover, the biological role of this pathway in the cellular response to hypoxia is not well defined. Here, by systematically screening protein stability using an N-terminome library, we reveal a broad set of cysteine-initiating proteins regulated by this pathway. Mutagenesis experiments further revealed the specificity of Cys-Arg/N-degron pathway, showing a preference for hydrophobic and positively charged residues following cysteine. Additionally, we uncovered full-length substrates that are regulated by this pathway during hypoxia, including IP6K1. Loss of IP6K1 impaired glucose uptake, glycolytic ATP production, and overall mitochondrial function. Consequently, IP6K1-deficient cells exhibited disrupted metabolic adaptation under hypoxic conditions and reduced survival under stress. These findings underscore the importance of the Cys-Arg/N-degron pathway in regulating metabolic responses and highlight its potential importance in hypoxia-related disorders.